Infliximab leads to a rapid but transient improvement in endothelial function in patients with primary systemic vasculitis. Issue 7 (16th December 2005) - Raza, K; Carruthers, D M; Stevens, R; Filer, A D; Townend, J N; Bacon, P A
Abstract : Objective: To assess the immediate effects of tumour necrosis factor α (TNFα) blockade on endothelial function in systemic vasculitis. Methods: Endothelial function was assessed by laser Doppler flowmetry in patients with active vasculitis after 10 infusions of infliximab. For comparison endothelial responses were assessed after five infusions of cyclophosphamide plus methylprednisolone. Results: Endothelial dependent vasodilatation (EDV) improved significantly within 24 hours of infliximab infusion. The median change in red blood cell flux (interquartile range) was 5.7 (4.3–8.2) before infusion v 8.4 (7.5–10.9) at 24 hours; p = 0.027. This was not maintained at day 14. No improvement was seen in EDV after cyclophosphamide plus methylprednisolone infusion. Conclusion: The rapid but transient improvement in EDV after TNFα inhibition suggests that TNFα may have a direct role in the impairment of endothelial function.